Gender diversity as determinants of firm's decisions and performance: role of moderators and corruption - Neha, Neha; Rubino, Franco Ernesto (My University, 2017)
The objective of this doctoral thesis is to provide insights to the literature on gender-diversity. Thus, all the work shares a common theme of gender-diversity, exploring how the specific features of female affect business activities and performance. In particular, three empirical chapters directly investigate the role of female representation in business on financial decisions and corporate performance, or indirectly the gender specific effect of corruption on firm value. The first chapter is an empirical analysis of the relationship between gender-diversity in management and debt maturity choice of firm for a sample of European corporations. It is aimed to reinforce the role of gender in determining the debt maturity choices, by implementing the role of national cultural moderators on the extent of the premised relationship. The second chapter examines how gender heterogeneity in management or board level affects the financial performance of the firm for a sample of European companies, by applying the national cultural factors as moderator. Finally, the third chapter investigates the relationship between the firm level corruption and financial performance of the firm for a sample of European enterprises, by highlighting the significance of gender-specific corruption in exploring the firm-level consequences of corruption. In summary, the empirical findings of all three chapters advocate that gender is one of the important dimensions of human capital and can reflect the functioning and decisions of company in multiple ways. Specifically, the outcomes of our empirical studies shed light on how the presence of female in the organization can contribute to improve the overall performance of the companies. The results recommend promoting women empowerment policies in order to effectively utilize this untapped and unique source of human capital. In addition, the last study evidence of firm-specific corruption effects on corporate performance emphasize that corruption in any form is not just a matter of ethics, but it is unbearable to have huge losses to enterprises value as it seems like a slow poison, gradually damaging the entire governing and management structure of any organization and it must be cured.
Dottorato di ricerca in Scienze economiche e aziendali, XXIX ciclo
Keywords: Gender diversity debt; Maturity masculinity corruptio; Ceo duality; Firm performance